Penggambaran Karakter Tokoh Siswa Indonesia dalam Naskah Skenario Film Yowis Ben 1 Karya Bayu Skak, Bagus Bramanti, dan Gea Rexy - Ananda Putriani; Suci Larassaty (Jurnal Bahasa dan Sastra, 2022)
This study aims to discuss the characters of Indonesian students in the screenplay of the film entitled Yowis Ben 1 by Bayu Skak, Bagus Bramanti, and Gea Rexy. The method used in this study is a descriptive method with content analysis techniques. The approach is done by analyzing and describing the object of the research. Qualitative analysis focuses on indicating the meaning, description, clarification, and placement of data in their respective contexts and often writes them down in the form of words. The data was taken from the scenatio script of the film Yowis Ben 1 by Bayu Skak, Bagus Bramanti, and Gea Rexy which the researchers transcribed through the films they had watched. The data analysis technique used in this research is qualitative content analysis. The results of this study indicate that the depiction of the characters emphasizes the technique of speaking or dialogue in the scenario script which includes the character's reactions, psychology, thoughts and feelings, as well as physical conditions in the Yowis Ben film scenario script 1. Narrative depiction technique is used by the author in the film Yowis Ben 1 to describe the behavior and physical depiction of characters rather than using dramatic depiction techniques. Dramatic techniques are mostly used to describe the psychological, thoughts and feelings of characters. Based on the results of the study, it was concluded that the reaction of the character in the form of action (guidance) and the way the character responded to a problem became things that could portray the character in a film screenplay.